Islam and assisted reproduction treatments: an empirical study on the relationship between science and religion in Tangier and Barcelona - Rosa Martínez-Cuadros (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
In recent decades there have been significant developments in assisted reproduction techniques, which have aided couples with difficulties in having children. These techniques have been well received in different parts of the world, and Muslim countries have been no exception. Adopting sociologist Michèle Lamont's theoretical perspective on "boundaries", semi-structured interviews were conducted with 20 health professionals and Islamic community leaders in the cities of Tangier and Barcelona during 2022. The aim of this article is twofold: first, to analyze how key actors in the Muslim community conceive of the relationship between Islam and science; second, to explain how this understanding is negotiated in relation to assisted reproduction treatments. The article concludes with a consideration of the complexities related to drawing the line between the positions of science and religion, and emphasized the importance of examining empirical cases in order to better capture the complex relationship between these two spheres and gain a deeper understanding of existing bioethical debates.